COMMUNITY EMPOWERMENT IN THE UTILIZATION OF USED GOODS WITH ECONOMIC VALUE TO INCREASING THE PRODUCTIVITY OF THE ENTREPRENEUR'S HOUSEWIFE IN THE VILLAGE OF KOTA JIN ATINGGOLA REGENCY NORTH GORONTALO - Risna Lose; Abd Mahmud Puloli; Abdul Rahmat; Ummyssalam ATAD Duludu; Pravin R. Choube (International Journal of Innovations in Engineering Research and Technology, 2023)
Higher education as an educational institution has the main task of carrying out the educational and teaching process, as well as carrying out research and community service. Community service is a process of self-empowerment for the benefit of the community. The implementation of service activities can bring changes to a better society. One of the forms of community service carried out by lecturers of the Faculty of Economics is to hold training by providing skills to housewives in the form of making creations of economically valuable products from used goods. After the training, it is hoped that housewives can develop product variations into goods that have high selling value and become successful entrepreneurs.